What Are the Ingredients for an Inequity Paradigm? Manipulating the Experimenter's Involvement in an Inequity Task with Dogs - Brucks, Désirée; Marshall-Pescini, Sarah; Essler, Jennifer L.; McGetrick, Jim; Huber, Ludwig; Range, Friederike (Frontiers in Psychology, 2017)
Cooperation is only beneficial if the outcome is equally shared between individuals involved in the cooperative interaction. A mechanism to limit the development of unequal cooperation is inequity aversion, the negative reaction to unequal treatment. While inequity aversion has been studied extensively across many animal species, it remains unclear whether inequity aversion elicited in experimental settings is directed to the cooperative partner animal or rather to the experimenter distributing the rewards unequally. In the current study we aimed to further investigate whether the presence of an experimenter distributing rewards is essential in order to elicit inequity aversion in dogs. We tested 22 dog dyads in an inequity task, requiring dyads to alternately press a buzzer in order to receive rewards of equal or unequal value. We manipulated the extent of the experimenter’s involvement in the task: in the experimenter-present version an experimenter gave a command to the dogs to press the buzzer and delivered the rewards by pushing the bowls into the dogs’ enclosure. In contrast, in the experimenter-absent version, no experimenter was visible and the buzzer and bowls were moved from behind a curtain. We found that dogs did not respond to the unequal treatment regardless of the experimenter’s involvement in the task. Nonetheless, we found that dogs based their behavior on frustration and social facilitation in the experimenter-absent version of the task, suggesting that a social interaction with an experimenter may be one aspect necessary to elicit inequity aversion. One potential explanation for the absence of inequity aversion in the experimenter-present version of the task might be the reward delivery method. Using separate sets of reward bowls for each dog instead of a shared bowl could have removed a potentially important competitive aspect (i.e. shared resource) from the paradigm. In addition, delivering the rewards via bowls, rather than directly handing the rewards to the dogs, might have caused dogs to perceive the task as less cooperative. These results suggest that both the presence of an experimenter causing inequity and the inclusion of a competitive or cooperative element in the task may be basic requirements for eliciting inequity aversion.